EXPLORING THE POTENTIAL OF LOCAL FOOD TO OPTIMIZE AS A TOURIST ATTRACTION IN LANTAN VILLAGE - Lalu Zul Yusri; Baiq Handayani Rinuastuti; Lalu M Furkan; Handry Sudiartha Athar; Didy Ika Supryadi (Bajang Institute, 2025)
Tourism villages contribute significantly to the local economy by integrating culture, nature, and cuisine as the main attractions. This study explores the potential of local food in Lantan Village as a strategic element in the development of community-based culinary tourism. Using a qualitative approach with a purposive sampling technique, data were obtained through in-depth interviews with stakeholders, including village officials, tourism awareness groups, culinary MSME actors, and tourists. The results of the study revealed that local foods such as komoh, wrap bible, bebetok, and sambal belling have not only culinary value but also contain philosophical meanings that strengthen the village's cultural identity. Typical processing techniques, such as the use of tanah sari to remove the bitter taste of papaya leaves in komoh, reflect innovations based on local wisdom that can increase tourist attractions. Tourists also show high interest in interactive experiences such as cooking traditional foods and following the coffee roasting process. Despite its great potential, culinary tourism in Lantan Village still faces challenges in the promotion and sustainability of culinary events such as